The protective role of ginsenoside Rg3 in heart diseases and mental disorders - Shi, Lili; Luo, Jinlan; Wei, Xiupan; Xu, Xizhen; Tu, Ling (Frontiers in Pharmacology, 2024)
Ginsenoside Rg3, a compound derived from Panax ginseng C. A. Mey., is increasingly recognized for its wide range of pharmacological effects. Under the worldwide healthcare challenges posed by heart diseases, Rg3 stands out as a key subject in modern research on Chinese herbal medicine, offering a novel approach to therapy. Mental illnesses are significant contributors to global disease mortality, and there is a well-established correlation between cardiac and psychiatric conditions. This connection is primarily due to dysfunctions in the sympathetic-adrenomedullary system (SAM), the hypothalamic-pituitary-adrenal (HPA) axis, inflammation, oxidative stress, and brain-derived neurotrophic factor (BDNF) impairment. This review provides an in-depth analysis of Rg3's therapeutic benefits and its pharmacological actions in treating cardiac and mental health disorders respectively. Highlighting its potential for the management of these conditions, Rg3 emerges as a promising, multifunctional therapeutic agent.